Campur Kode Bahasa Indonesia-Arab sebagai Strategi Komunikatif dalam Vlog YouTube Konteks Akademik-Religius - Izzatin Awalia Wahidah; Fadlil Yani Ainusyamsi; Dayudin Dayudin (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
This study focuses on identifying the forms of code-switching and analyzing the factors that influence it in the YouTube vlog content of Abdurrahman Hafnizar entitled “Suasana Kelas Universitas Islam Madinah 2023.” Employing a sociolinguistic approach and a descriptive qualitative method, this research examines language use in social and digital contexts. The research data includes all spoken utterances containing Indonesian-Arabic code-switching, collected through participant observation and recording techniques from a vlog video with a duration of 10 minutes and 17 seconds. Data analysis was conducted intralingually to classify code-switching forms based on linguistic structure, and extralingually to examine the underlying social factors. The findings reveal that code-switching appears in various forms, namely the insertion of words, phrases, baster, and clauses. Among all these forms, word and phrase insertions dominate, indicating that code-switching most frequently occurs at the lexical level in spontaneous communication. The main driving factors for code-switching include the use of more familiar and efficient terms, the speaker's personal background and language habits, and the influence of interlocutors. This underscores the role of social identity and interaction in bilingual communities. Functionally, code-switching serves as a communication strategy to reinforce the speaker's academic and religious identity in digital media. This study contributes to digital sociolinguistics by integrating Suwito's classification of code-mixing forms with Suandi's framework of factors. However, this research is limited to a single vlog data source, and it is suggested that future studies explore broader data sources and more diverse analytical approaches.